Prevalence and clonal nature of Escherichia coli O157:H7 on dairy farms in Wisconsin. - Faith, N G (1996)
A survey was conducted between March and October of 1994 to determine the prevalence and identify the sources of serotype O157:H7 isolates of Escherichia coli in Wisconsin dairy herds. A stratified sample of 400 farms was identified, and 70 farms with weaned calves less than 4 months old were included in the study. During the prevalence study, 5 of the 70 farms (herd prevalence, 7.1 +/- 4.5%) and fecal samples from 10 of 560 calves (animal prevalence, 1.8%) tested positive for serotype O157:H7. In a follow-up study, the five O157:H7-positive farms and seven of the O157:H7-negative farms identified in the prevalence study were visited again. An additional 517 fecal samples from cattle of various ages were tested, and a total of 15 animals from four of the five herds that were previously positive and 4 animals from two of seven herds that were previously negative tested positive for E. coli O157:H7. Observations made during the follow-up study suggested that horizontal transmission was an important means of E. coli O157:H7 dissemination on the farms. A total of 302 environmental samples, were examined, and 2 animal drinking water samples from one previously negative farm and 1 animal drinking water sample from a previously positive farm contained E. coli O157:H7. Analyses by the pulsed-field gel electrophoresis technique of contour-clamped homogeneous electric field electrophoresis revealed that isolates from the same farm displayed identical or very similar XbaI restriction endonuclease digestion profiles (REDP), whereas isolates from different farms typically displayed different REDP. However, more than one REDP was usually observed for a given herd over the 8-month sampling period. Analyses of multiple isolates from an animal revealed that some animals harbored O157:H7 strains that had different REDP, although the REDP of isolates obtained from the same fecal sample were very similar. Collectively, 160 bovine isolates obtained from 29 different animals and three water isolates displayed 20 distinct XbaI REDP. Our data revealed that there are several clonal types of serotype O157:H7 isolates in Wisconsin and indicated that there is probably more than one source of this pathogen on the dairy farms studied. However, animal drinking water was identified as one source of E. coli O157:H7 on one farm.